(untitled) (Quinto Sol, 2025)
This article examines the intersection of politics, higher education, and the media in Tucumán during the first Peronist government, in Argentina. It analyzes the creation of the morning newspaper Trópico by the National University of Tucumán in 1947, exploring how this medium emerged as a political and communication response from local university Peronism to the predominance of the opposition newspaper La Gaceta. The study addresses both national and local policies regarding universities and the media under Peronism, highlighting the situation of the university and the local press. Additionally, it explores the editorial profile of Trópico, its alignment with the government, and its stance towards opposition media. Although Trópico represented an original attempt to counteract the opposition’s influence by disseminating the official narrative, it did not receive significant support from the government, and its impact was limited.